Pembentukan Remaja Sadar Bencana dan Pelatihan Mitigasi Bencana di SMP Muhammadiyah 1 Turi: Formation of Disaster-Aware Youth and Disaster Mitigation Training at SMP Muhammadiyah 1 Turi - Listyaningrum, Tri Hapsari; Dewi, Ratih Kusuma; Puspito, Heri; Rohmah, Astika Nur (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2024)
Mount Merapi, located in Sleman Regency, is one of the most active volcanoes in the world, with eruption intervals ranging from 3 to 7 years. In this community service project, we aim to establish a Disaster-Aware Youth Group and conduct Disaster Mitigation Training at SMP Muhammadiyah 1 Turi. The goal of this community service is to form a group of disaster-aware youth volunteers at SMP Muhammadiyah 1 Turi. The community service method involves disaster preparedness education for 34 students, providing them with both knowledge and practical experience through role-playing and disaster simulation exercises. As a result of this project, a group of disaster-aware youth volunteers has been established at SMP Muhammadiyah 1 Turi. Additionally, posters about disasters and health were created, along with the development of evacuation routes and assembly points. In conclusion, the community service project by the Unisa Yogyakarta lecturers at SMP Muhammadiyah Turi Yogyakarta was successful. The establishment of disaster-aware youth volunteers at SMP Muhammadiyah Turi has been achieved, posters have been installed, and evacuation routes and assembly points have been established. Students' knowledge about disaster preparedness has improved.